2012
DOI: 10.1371/journal.pone.0041628
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between In Vivo Biofilm Formation and Virulence Gene Expression in Escherichia coli O104:H4

Abstract: The emergence of novel pathogens poses a major public health threat causing widespread epidemics in susceptible populations. The Escherichia coli O104:H4 strain implicated in a 2011 outbreak in northern Germany caused the highest frequency of hemolytic uremic syndrome (HUS) and death ever recorded in a single E. coli outbreak. Therefore, it has been suggested that this strain is more virulent than other pathogenic E. coli (e.g., E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 34 publications
2
70
0
Order By: Relevance
“…We further identified the main site of C227-11 colonization to be the cecum in both Amp-treated and ICF models, a finding that is in agreement with the findings obtained with other O104:H4 infection models (47,49,68). However, unlike Torres et al (47), we found that the O104:H4 outbreak strain clearly also colonized the small and large intestines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We further identified the main site of C227-11 colonization to be the cecum in both Amp-treated and ICF models, a finding that is in agreement with the findings obtained with other O104:H4 infection models (47,49,68). However, unlike Torres et al (47), we found that the O104:H4 outbreak strain clearly also colonized the small and large intestines.…”
Section: Discussionsupporting
confidence: 91%
“…is earlier than the time that it had been detected in a germfree mouse model, in which similar kidney damage was not noted in O104:H4-infected mice at 7 days p.i., though acute tubular necrosis was identified in mice euthanized on days 13 to 15 p.i. in that study (49). There have been a few publications describing acute tubular necrosis in the kidneys of STEC-infected individuals.…”
Section: Discussionmentioning
confidence: 85%
“…Sci-1 and sci-2 are two gene clusters present on pheU responsible for evidence for enhanced virulence and detrimental effects caused by emerging heterogeneity among strains. 12 Transmission of EAEC is most commonly associated with contaminated food and water. In Mexico, EAEC is the most common bacterial pathogen isolated from food.…”
Section: Introductionmentioning
confidence: 99%
“…DgcT (YcdT) is a DGC that has been implicated in the production of poly-GlcNAc (PGA), which is expressed within the host and serves as biofilm matrix component and/or virulence factor in some pathogenic E. coli (48)(49)(50). We found that the dgcT gene was entirely deleted in 14 strains and disrupted by small frameshift or stop codon mutations in five additional strains (Table 2).…”
Section: Resultsmentioning
confidence: 99%